Could Culling of Elephants Be Considered Inhumane and Illegal in South African Law?. Issue 3 (2nd October 2021) - Slotow, Rob; Blackmore, Andrew; Henley, Michelle; Trendler, Karen; Garaï, Marion
Abstract: Elephant culling is included in National Norms and Standards for the Management of Elephants in the Republic of South Africa, as a last-resort option to reduce elephant population size when required to meet reserve objectives. Recent judgments in South African courts have emphasised the importance of considering animal welfare in conservation. We assess the approved method of culling elephant family units, in terms of the legal and policy framework in South Africa, as well as considering elephant welfare and wellbeing. We find that the current culling method is likely to be inhumane, and potentially inconsistent with the Constitution, as interpreted by the judiciary. In addition, in certain circumstances, culling is illegal in terms of the Animals Protection and Meat Safety Acts, and contravenes World Organisation for Animal Health and global standards for the slaughter of animals. We recommend considering a moratorium on culling of elephant family units, as well as of lone bulls, until humane slaughter methods, and standard operation procedures that ensure an extremely high probability of instantaneous ("clean") kill, are developed and approved. We recommend an ethics review process for conservation management interventions involving wellbeing risks to animals, such as is required for animal research. Notwithstanding other imperatives that need consideration, conservation practice should better balance welfare, to align with both South African legislation and global norms.